The Role of Digital Game-Based Learning in Enhancing Self-regulated Learning Strategies: A Case Study Among Bina Mandiri Gorontalo University Students - Haspin Umar; Radit Pakudu; Meilan Matiti (Journal of Educational Technology and Innovation, 2025)
This study aims to explore the role of Digital Game-Based Learning (DGBL) in improving Self-Regulated Learning (SRL) in students of Bina Mandiri Gorontalo University. Using a qualitative approach with a case study design, data was collected through in-depth interviews, participatory observations, and documentation of 30 students from the Educational Technology, Management, and Pharmacy study programs. The results of the study show that DGBL has a positive impact on the development of student SRL, especially in the aspects of learning planning, time management, motivation regulation, and self-evaluation. Students take advantage of the interactive and flexible features of digital games to set the rhythm and learning strategies according to their individual needs. However, challenges were also found such as potential distractions due to focusing too much on the game elements. In general, these findings reinforce that DGBL can be an effective alternative learning strategy that is relevant to the current context of higher education, especially in building student learning independence. This research is expected to be the basis for the development of digital learning policies in universities, especially in developing regions.